Indian and International Strategies of internal displacement: An overview under International Humanitarian Law - V.S, AbidhaBeegum (International Journal of Psychosocial Rehabilitation, 2020)
Internal displacement is a crucial issue in 21st century, and black label upon the great history of many nations. This term still creating confusion on the aspect that, whether it is the byproduct of national law or international law. Since it is not a settled issue, the humanitarian and human rights aspects of internal displacement is much more complicated and not addressed properly. This paper is trying to analyze the responsibility part to establish the very essence of international humanitarian law upon internal displacement.